Long Non-coding RNA Double Homeobox A Pseudogene 8: A Novel Oncogenic Propellant in Human Cancer - Xue, Chen; Cai, Xiaolu; Jia, Junjun (Frontiers in Cell and Developmental Biology, 2021)
A growing number of studies are reporting important roles played by long noncoding RNAs (lncRNAs) in various pathological and physiological processes. LncRNAs are implicated in numerous genomic regulatory functions at different levels, including regulation of transcription, post-transcriptional processes, genomic stability, and epigenetic genome modifications. Double homeobox A pseudogene 8 (DUXAP8), a novel lncRNA, has been reported to be involved in many cancers, including gastric, colorectal, esophageal, bladder, oral, ovarian, lung, and pancreatic cancers as well as hepatocellular carcinoma. DUXAP8 plays specific oncogenic roles via numerous malignancies promoting pathways. DUXAP8 is frequently dysregulated in multiple cancers, acting as a sponge to downregulate various tumor-suppressing microRNA activities. In this review, we comprehensively explore DUXAP8 expression and prognosis across cancer types, and systematically summarize current evidence concerning the functions and molecular mechanisms of DUXAP8 in tumorigenesis and progression. We conclude that DUXAP8 is a potential biomarker and therapeutic target for multiple cancers.